Penatalaksanaan Pemeriksaan MRI Cervical Pada Kasus Syringomyelia Pada Medulla Spinalis Di Rumah Sakit Primaya Tangerang - Hanisa Hanisa; I Putu Eka Juliantara; Edwien Setiawan Saputra (Pusat riset dan Inovasi Nasional, 2023)
Management of Cervical MRI Examination in Cases of Syringomyelia in the Spinal Medulla at Primaya Hospital Tangerang. Magnetic Resonance Imaging (MRI) is a state-of-the-art diagnostic tool for examining and detecting the body using a large magnetic field and radio frequency waves, without the use of X-rays or radioactive materials, which produces cross-sectional images of the human body/organs using a magnetic field. strength between 0.064 – 1.5 tesla (1 tesla = 1000 Gauss) and vibrational resonance of the hydrogen atom nucleus. MRI can produce images of the vertebral column, spinal cord, and also the CSF. The MRI screening procedure is ideal for the differential diagnosis of structural disorders that can affect the spinal roots and spinal cord. This examination is used in carrying out a vertebral examination at once, namely scanning starting directly from the cervical vertebrae and also up to the sacrum. So this examination can directly diagnose the cervical, thoracic, lumbar, sacral vertebrae and also includes the coccyx. The purpose of this study was to determine the management of cervical MRI examination with clinical syringomyelia. This research is descriptive qualitative with a case study approach. The subject is a patient with clinical syringomyelia. All subjects underwent Cervical MRI examination at 1.5 tesla to find out the sequence and procedure and sequence information used. From the research results obtained according to the theory using T1-weighted imaging with administration of contrast agent. While in the field using the cervical MRI protocol without contrast, it is sufficient to establish a diagnosis using an examination procedure with a localizer sequence design, sagittal T1, Axial T1 FSE, Axial T2, Axial 2D marge, sagittal T2 fat sat, Axial T2 thoracic 2-3, myelo 2D. The T2 fat sat sagittal sequence section makes it possible to see the anatomy, namely syringomyelia.